On Genetic Programs and Feedback Networks. - Dougherty, Stephen (Configurations)
The article focuses philosophical views on genetic programs and feedback networks citing several books and writings including "Emergence," by Steven Johnson and "Darwin's Radio," by Mark Taylor. "Darwin's Radio," portrays the techno-mediazation of society and assents to a bioinformatics that reduces people to mere conduits for information.